Treatment of food processing wastewater in anaerobic-aerobic filter bioreactor with commercial inoculum performance and bacterial community changes - Wynn, Ni Lar
In view of the need to develop better treatment systems for food processing wastewater, this study explores the potential of a continuous four-stage anaerobic - aerobic biofilter reactor system, which was seeded with commercially available inoculum powder. The performance of the process configuration was investigated in small-scale assembly of reactors and a larger scale baffled bioreactor, using various model wastewaters containing sucrose, peptone, wheat starch and cassava starch. The hydraulic retention time (HRT) was 12-24 h while the organic loading rates were 0.5 to 10.3 g COD/L/d. In the treatment of simple substrate such as sucrose at low concentration and 0.5 g COD/L/d, 91 percent of COD was removed and most of the COD removal (80 percent) was accomplished in the first anaerobic reactor of 4.8 h HRT. In the treatment of cassava starch, COD removal was ca. 60 percent after the anaerobic reactor and 80 percent after the aerobic reactor. In small-scale system, a similar performance was obtained for sucrose wastewater. In treating peptone wastewater in the latter system, the largest removal of COD occurred in the first anaerobic reactor, but the role of the succeeding anaerobic and aerobic reactors were significant. In starch wastewater, acid formation prevails over methane formation, thus, resulting in low pH levels that are deemed inhibitory to methanogens and even to the aerobic microorganisms in the last step of the system. Microbial community composition profile was determined in the inoculums and the biofilm that developed inside the series of reactors for various wastewater using polymerase chain reaction - denaturizing gradient gel electrophoresis (PCR-DGGE). The DGGE profile show a much more diverse microbial community in peptone wastewater than in low concentration sucrose wastewater and high concentration starch wastewater. Analysis of the dominant DGGE bands show that the dominant microorganisms. The community that developed in anaerobic and aerobic reactors for starch wastewater did not vary much, owing to the low pH that can inhibit activity of aerobic microorganisms.